Elucidating the Probiotic Potential of Lactobacillus and Bifidobacterium Species in Modulating Glucose Metabolism and Inflammation in Gestational Diabetes Mellitus: A Scoping Review - Sidra A Uzair (23124226) (2025)
Gestational diabetes mellitus (GDM) affects 14% of pregnancies globally, contributing to gut microbial dysbiosis, inflammation, and insulin resistance. Probiotic supplementation with Lactobacillus and Bifidobacterium species has potential in addressing GDM by modulating gut microbiota. However, findings from clinical trials are inconsistent. In this scoping review, the evidence on the role of Lactobacillus- and Bifidobacterium-based probiotic supplementation in managing GDM is mapped systematically, and knowledge gaps and future research directions are identified. Following Arksey and O’Malley’s framework, an initial database search was conducted in February 2023 across 4 literature databases for articles on randomized controlled trials published since 2013; a second search in January 2025 included studies published after February 2023, reflecting ongoing research in this field. Title and abstract screening were conducted using Rayyan, followed by full-text review, yielding 29 eligible studies. Cohen’s d was used to quantify the magnitude of the effect. The interventions included encapsulated probiotics or fermented foods containing various Lactobacillus and Bifidobacterium species. The findings consistently showed improvements in fasting glucose levels, insulin sensitivity, and reduction in serum insulin levels and homeostatic model assessment for insulin resistance with increased Quantitative Insulin Sensitivity Check Index scores. Improvements in glucose metabolism were linked to short-chain fatty acids (SCFAs), activating G-protein coupled receptors (GPRs), boosting GLP1 secretion, and insulin release. Probiotic interventions also favorably modulated inflammatory markers (high-sensitivity C-reactive protein, interleukin-6 [IL-6], and tumor necrosis factor-α), likely through enhanced mucus production, SCFAs binding to GPR109, strengthening tight junctions, and concurrent release of IL-18 and IL-10. The evidence indicates the potential of Lactobacillus- and Bifidobacterium-based probiotic interventions to beneficially influence glucose metabolism, inflammatory response, and gut microbial balance in GDM. Heterogeneity in probiotic formulations across studies, probiotic doses, and regional differences in diet and lifestyle underscore the need for more targeted and standardized research to fully understand the therapeutic potential of probiotics in GDM. Other Information Published in: Nutrition Reviews License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/nutrit/nuaf238